Sosialisasi Penggunaan, Manfaat dan Bahaya Media Digital Handphone pada Anak SMPN 2 Nagawutung Kabupaten Lembata - Emiliani Hoi Muda; Angela Dewi Sartiani Rua; Donna Isra Silaban; P. Hendrikus Saku Bouk (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The advancement of technology today has made digital media a necessity that often leads to dependency, especially among teenagers. Junior high school students need guidance in using technology so they can access social media wisely, in order to develop a positive character. KKN-T students from UNWIRA Kupang conducted community service through observation and visits to SMPN 2 Nagawutung, which revealed that many students are using their mobile phones inappropriately, resulting in a decline in interest and talent. The methodology of the service includes mentoring, training, and socialization to educate students about the proper use of digital media. Although social media offers many benefits, such as access to vast information and educational resources, misuse can have negative consequences, including addiction and the spread of hoaxes. Therefore, education, socialization, and assistance in the use of digital media are very important for the development of children.